The contents of contracts and unfair terms - Chen-Wishart, Mindy; Vogenauer, Stefan, 1968- (Oxford : Oxford University Press, 2020)
The 'Studies in the Contract Laws of Asia' series charts the divergence in and common principles of contract laws across Asia, with a view to providing the scholarly foundations for future harmonization and reform. This third volume deals with the contents of contracts and unfair terms.
This edition also issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on November 4, 2020).
Keywords: Contracts -- Asia; Clauses (Law) -- Asia; Law; Laws of specific jurisdictions & specific areas of law